Gaya Hidup Flexing Masyarakat Kecamatan Pontianak Kota Dalam Perspektif Ekonomi Syariah - Prilijayanti, Dewi; Ruslan, Ismail; Syahbudi, Syahbudi; Safri, Hayanuddin (CV. ITTC INDONESIA, 2025)
The phenomenon of flexing lifestyle—showing off luxury goods, social status, or personal achievements—has become increasingly prevalent among housewives in Pontianak Kota District along with the rapid growth of social media. This study aims to explore the role of social media in encouraging flexing behavior, the dynamics of social competition in building self-image, and its impact on household financial management. This research employed a qualitative descriptive approach with in-depth interviews and participatory observation. The findings reveal that social media significantly influences flexing practices, particularly through the consumption of branded goods, participation in social activities, and engagement with fashion and beauty trends. Such behavior has economic implications, including higher consumptive spending and the potential risk of financial imbalance within households. From an Islamic economic perspective, flexing contradicts the principle of al-iqtisad (moderation) and tends to lead to israf (wastefulness). Therefore, Islamic financial literacy is urgently needed to foster wise consumption patterns and promote sustainable family welfare.